2024
DOI: 10.1186/s12865-024-00599-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive biomarkers for immune-related adverse events in cancer patients treated with immune-checkpoint inhibitors

Jingting Wang,
Yan Ma,
Haishan Lin
et al.

Abstract: Purpose The objective of this study was to identify potential predictors of immune-related adverse events (irAEs) in cancer patients receiving immune checkpoint inhibitor therapy among serum indexes, case data, and liquid biopsy results. Methods We retrospectively analyzed 418 patients treated with anti-programmed cell death 1(PD-1)/PD-1 ligand (PD-L1) inhibitors from January 2018 to May 2022 in our cancer center. We identified factors that correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Additionally, anthropometric measurements such as waist circumference and waist-hip ratio, as well as image-based measures such as computed tomography or magnetic resonance imaging can be used to characterize obesity as well; however, they could not be obtained from medical records in this study and may be collected prospectively in the follow-up [ 17 , 45 , 46 ]. Finally, it has been shown that BMI is positively correlated with the incidence of immune-related adverse events (irAE) [ 47 ]; however, since this study focused on the relationship between BMI and prognosis of chemoimmunotherapy combinations, the analysis regarding irAE was not performed, but we plan to do so in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, anthropometric measurements such as waist circumference and waist-hip ratio, as well as image-based measures such as computed tomography or magnetic resonance imaging can be used to characterize obesity as well; however, they could not be obtained from medical records in this study and may be collected prospectively in the follow-up [ 17 , 45 , 46 ]. Finally, it has been shown that BMI is positively correlated with the incidence of immune-related adverse events (irAE) [ 47 ]; however, since this study focused on the relationship between BMI and prognosis of chemoimmunotherapy combinations, the analysis regarding irAE was not performed, but we plan to do so in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable efforts by investigators to develop biomarkers for predicting irAEs, a reliable and definite indicator remains elusive to date [86]. Nevertheless, with ongoing research aimed at creating tools that improve predictions by integrating multiple indicators, it is anticipated that forthcoming research will enhance predictive precision through more comprehensive and sophisticated studies [87].…”
Section: Discussionmentioning
confidence: 99%